Turlough vegetation communities : links with hydrology, hydrochemistry, soils and management - Sharkey, Nova (Trinity College (Dublin, Ireland). Department of Botany, 2012)
This thesis documents the vegetation communities of 22 turloughs from Counties Galway, Clare, Roscommon and Mayo. In total, 28 vegetation communities were identified, classified and described. These communities ranged from the fully aquatic to mostly terrestrial, with a range of intermediate vegetation types in between. There was a degree of overlap between the species composition of many of the plant communities; few species were faithful to a single plant community.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.